RECENT FIXED POINT THEOREMS FOR T-CONTRACTIVE MAPPINGS AND T-WEAK (ALMOST) CONTRACTIONS IN METRIC AND CONE METRIC SPACES ARE NOT REAL GENERALIZATIONS - Bekeshie, T.; Naidu, G.A (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
The purpose of this research article is to show that recent fixed point theorems obtained in metric and cone metric spaces for T-contractive mappings and TW-contractions are equivalent to previously existing theorems in the literature; hence are redundant. We also show that Proposition 2.5 of [4] is invalid.